Mitigation Of Loss Circulation Problems Using Calcium Carbonate In Well 'HF-05', 'Kanaan' Field - Heldy Febryanto; Firdaus; Risna; , Abdul Gafar Karim; Aprilino Alfa Kurmasela; Darmiyati, Iin; Annisa Efidiawati (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
Lossicirculation isione of theiproblems thatioften occursiin theidrillingiworld where loss of circulation or loss of circulation of mud is interpreted as a loss of circulation in a small amount or all of the drilling mud when it is circulated, so that when the drilling takes place, the circulated mud enters the drilling zone. penetrated formation. The